2016
DOI: 10.1002/cphc.201600757
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Torsional Dynamics of Two Methyl Groups in 2‐Acetyl‐5‐methylfuran as Observed by Microwave Spectroscopy

Abstract: The molecular-beam Fourier transform microwave spectrum of 2-acetyl-5-methylfuran is recorded in the frequency range 2-26.5 GHz. Quantum chemical calculations calculate two conformers with trans or cis configuration of the acetyl group, both of which are assigned in the experimental spectrum. All rotational transitions split into quintets due to the internal rotations of two nonequivalent methyl groups. By using the program XIAM, the experimental spectra can be simulated with standard deviations within the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 28 publications
6
55
1
Order By: Relevance
“…The planar moment of inertia P cc =−2 ( I c − I a − I b )=13.396 u Å 2 of OMA confirms that the heavy atom skeleton is planar with two pairs of hydrogen atoms out of plane. These values are very similar as that found in other planar molecules containing two methyl groups such as the trans and cis conformers of 2‐acetyl‐5‐methylfuran ( P cc =12.938 and 13.160 u Å 2 , respectively) and the syn and anti conformers of 3,4‐dimethylbenzaldehyde ( P cc =12.904 and 12.938 u Å 2 , respectively) …”
Section: Figuresupporting
confidence: 86%
See 2 more Smart Citations
“…The planar moment of inertia P cc =−2 ( I c − I a − I b )=13.396 u Å 2 of OMA confirms that the heavy atom skeleton is planar with two pairs of hydrogen atoms out of plane. These values are very similar as that found in other planar molecules containing two methyl groups such as the trans and cis conformers of 2‐acetyl‐5‐methylfuran ( P cc =12.938 and 13.160 u Å 2 , respectively) and the syn and anti conformers of 3,4‐dimethylbenzaldehyde ( P cc =12.904 and 12.938 u Å 2 , respectively) …”
Section: Figuresupporting
confidence: 86%
“…If not stated otherwise, the MP2/6–311++G(d,p) level of theory is used. We choose this level, because it yields quite reasonable results for some other molecules containing aromatic rings like phenetole, 2,5‐dimethylthiophene, and 2‐acetyl‐5‐methylfuran …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There are also some microwave spectroscopic studies on ketones with LAM(s) reported in the literature, i.a. methyl vinyl ketone, methyl isobutyl ketone and methyl neopentyl ketone, or some unsaturated ketones such as allyl acetone, and 2‐acetyl‐5‐methylfuran . The torsional barrier height of the acetyl methyl group in these ketones varies in a wide range from about 170 cm −1 to 440 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Since decades, this is proven by the fact that many analysis methods have been developed to determine the three-dimensional structure of a molecule. Only a very limited number of microwave spectroscopic investigations on similar aromatic systems with two internal rotors are reported in the literature, e. g. 2,5-dimethylfurane, [5] 2,5-dimethylthiophene, [6] 2-acetyl-5-methylfuran, [7] and dimethylbenzaldehyde. In the gas phase, molecular jet Fourier transform microwave (FTMW) spectroscopy is the most suitable tool for this purpose.…”
Section: Introductionmentioning
confidence: 99%